Optimal locations and electricity prices for dynamic wireless charging links of electric vehicles for sustainable transportation - Liu, Haoxiang; Zou, Yuncheng; Chen, Ya; Long, Jiancheng (Transportation research. Part E, Logistics and transportation review, 2021)
Electric vehicles are one of the effective tools for pollution reduction and sustainable transportation in emerging markets. In this paper, we investigate the optimal locations and electricity prices for dynamic wireless charging links of electric vehicles to minimize total social cost within a given budget while ensuring nonnegative operating profit to alleviate a government’s operational pressure. A logit-based stochastic user equilibrium model is proposed to capture drivers’ routing and recharging behavior, and a linear programming approach is developed to determine a path recharging plan. The problem is rendered as a bi-level formulation and solved using an efficient surrogate model-based algorithm.